A randomized controlled trial to enhance coping and posttraumatic growth and decrease posttraumatic stress disorder in HIV-Infected men who have sex with men in Beijing, China. Issue 6 (3rd June 2018) - Ye, Zhi; Yu, Nancy Xiaonan; Zhu, Wanling; Chen, Lihua; Lin, Danhua
ABSTRACT: Although HIV-infected men who have sex with men (MSM) constitute a newly emerged high-risk group in China, little research outside Western countries is available on effective intervention programs to enhance their well-being. The purpose of this randomized controlled trial was to evaluate the efficacy of a group intervention program designed to improve the well-being and adaptive coping strategies of 60 HIV-infected MSM in Beijing, China, randomly assigned either to the intervention group for participation in four weekly sessions or to the control group for placement on a waiting list. They all completed measurements at pre- and postintervention. Compared with the control group, the intervention group reported significantly increased problem-focused coping strategies and levels of posttraumatic growth (PTG) as well as decreased symptoms of posttraumatic stress disorder (PTSD) at the completion of the intervention. In addition, mediation analysis showed that changes in problem-focused coping strategies mediated the intervention effect on increases in PTG; however, the mediating effect of coping strategies on the association of intervention and PTSD was not significant. This study provides empirical evidence for conducting psychological intervention to promote the well-being of HIV-infected MSM. The findings also elucidate the mechanism through which intervention improved PTG.